The effect of motorcycle helmet type on head response in oblique impact - N. Q., Radzuan; Mohd Hasnun Ariff, Hassan; Mohd Nadzeri, Omar; Nur Aqilah, Othman; M. A., Mohamad Radzi; K. A., Abu Kassim (Universiti Malaysia Pahang, 2023)
In Malaysia, riding motorcycles is a popular mode of transportation, particularly in urban areas where traffic congestion is prevalent. Additionally, motorcycles are relatively affordable and have low fuel consumption, which makes them an attractive option for many. Per Malaysian traffic laws, riders must wear helmets while riding. As a result, various brands and types of helmets are available for purchase. However, with the increasing popularity of online shopping platforms, many individuals opt to purchase helmets online despite the uncertain quality control of these products. This study aims to assess the effectiveness of three different types of motorcycle helmets in protecting the head from injury. The helmet types evaluated in this unbiased study include full-face, open-face, and half-coverage helmets. The head injury predictors used in this study include Peak Linear Acceleration (PLA), Peak Rotational Acceleration (PRA), Head Injury Criterion (HIC), and Brain Injury Criterion (BrIC). Each helmet was subjected to an impact in a controlled environment using a 6-kg cylinder attached to a pendulum arm, with the impact directed at the front of the helmet at a speed of approximately 6 m/s. Full-face and open-face helmets performed exceptionally well in terms of linear parameters (PLA and HIC). The PLA and HIC of half-coverage helmets are nearly 70% and 50% higher than full-face and open-face helmets. All helmets perform poorly against rotational impact (PRA and BrIC). This shows that helmet design needs to be improved to enhance protection against rotational impact. This study represents the first case study in Malaysia to gather mechanical head injury data comparing the protective performance of different helmet types under both linear and rotational impact. These findings may provide a more accurate understanding of helmet performance in protecting against head injuries.